2018
DOI: 10.1175/jcli-d-17-0109.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Air–Sea Interaction in the 30–60-Day Boreal Summer Intraseasonal Oscillation over the Western North Pacific

Abstract: This study investigates the role of air–sea interaction in the 30–60-day boreal summer intraseasonal oscillation (BSISO) over the western North Pacific with daily outgoing longwave radiation (OLR), CFSR, and OAFlux datasets for 1985–2009. The BSISO events are identified with the first principal component of 30–60-day bandpass filtered OLR anomalies. Composite analysis of these events reveals that during the northward migration of BSISO, the convection can interact with underlying sea surface temperature (SST).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 103 publications
5
38
0
Order By: Relevance
“…The southerlies become much stronger over the Bay of Bengal (Figure 1a), which transport the enhanced hmi near the convective center to the north (Figure 10). À v·∂m 0 =∂y h ialso enhances northward propagation over the South China Sea and western Pacific, as revealed by Wang et al (2018), in which they reported the importance of the anomalous moisture by mean meridional wind (À v·∂q 0 =∂y h i ) to the northward propagation of convection. The anomalous hmi advection by the anomalous zonal wind (Àu 0 · ∂m 0 /∂x) is negative over the South China Sea, largely inhibiting propagation.…”
Section: Quantitative Contributions Of Mse Budget Terms and Sst Variamentioning
confidence: 86%
See 3 more Smart Citations
“…The southerlies become much stronger over the Bay of Bengal (Figure 1a), which transport the enhanced hmi near the convective center to the north (Figure 10). À v·∂m 0 =∂y h ialso enhances northward propagation over the South China Sea and western Pacific, as revealed by Wang et al (2018), in which they reported the importance of the anomalous moisture by mean meridional wind (À v·∂q 0 =∂y h i ) to the northward propagation of convection. The anomalous hmi advection by the anomalous zonal wind (Àu 0 · ∂m 0 /∂x) is negative over the South China Sea, largely inhibiting propagation.…”
Section: Quantitative Contributions Of Mse Budget Terms and Sst Variamentioning
confidence: 86%
“…Therefore, our "SST effect" may be slightly underestimated. Wang et al (2018) found that the intraseasonal SST anomalies could induce boundary layer moisture convergence and increase surface turbulent flux anomalies, which tend to heat and moisten the boundary layer, favoring the northward propagation of BSISO. Based on our diagnostics, intraseasonal SST variability contributes up to 20% to the propagation of convection (∂hmi/∂t).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the internal atmospheric processes, the effects of air-sea interaction in promoting the NP of BSISO have also been demonstrated by many studies (Kemball-Cook and Wang 2001;DeMott et al 2013DeMott et al , 2015Wang et al 2018b;Gao et al 2019). BSISO convection influences the sea surface temperature (SST) through regulating solar radiation, heat fluxes, and mixed-layer entrainment, but the feedback effects of SST anomalies (heating, moistening, and destabilizing the low-level atmosphere) also have significant impacts on the BSISO activity (Kemball-Cook and Wang 2001;Fu et al 2003;Fu and Wang 2004;Wang et al 2018b). Fu and Wang (2004) found that the BSISO activity and its relationship with the underlying SST are more realistic in a coupled model and the ISO is approximately 50% stronger in a coupled model than in the atmosphere-only model (Fu et al 2003).…”
Section: Introductionmentioning
confidence: 99%